Leopardi : selected poems - Leopardi, Giacomo, 1798-1837 (Lockert library of poetry in translation., 1997)
By catching something of Leopardi's cadences and tonality in a version that still reads as idiomatic modern English (with an occasional Irish or American accent), Leopardi: Selected Poems should win for the Italian poet the wider appreciative audience he deserves. Hist themes are mutability, landscape, love; his attitude, one of unflinching realism in the face of unavoidable human loss. But the manners of the poems are a unique amalgam of philosophical toughness and the lyrically bitter sweet. In a way more pure and distilled than most others in the Western tradition, these poems are truly what Matthew Arnold asked all poetry to be, a "criticism of life." The translator's aim is to convey something of the profundity and something of the sheer poetic achievement of Leopardi's inestimable Canti.